CLINICAL NEUROLOGICAL AND DIAGNOSTIC ASPECTS OF HEADACHES WITH CONGENITAL PRECEREBRAL ANGIODYSPLASIA - Khalimova, Kh.M.; Rakhmatullaeva, RG.K.; Rashidova, N.S.; Parpieva, Yu.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the clinical, neurological and diagnostic aspects of headaches in congenital pre-cerebral angiodysplasia. Materials and Methods: There were 213 patients with headaches under our supervision. The core of the studied cohort was migraine patients, which amounted to 179 (100%) cases, among them migraine with angiodysplasia- (MSA) was 136 (45.9%), followed by patients with migraine without angiodysplasia (IBA) – 43 (14.5%), tension headache (HDN) – 26 (8.8%), cluster headache (KGB) – 8 (2.7%) patients. The study used clinical neurological, neuropsychological, neuroimaging and statistical methods. Results: Migraine can develop in people with congenital pre-cerebral angiodysplasia in 76% of cases, and in people without congenital abnormalities of cerebral vessels – 24%. At the same time, patients with congenital pre-cerebral angiodysplasias most often develop migraine with aura in 62.5% of cases, whereas without it its simple form is 88.4%. Indicators of the scale of YOUR, MIDAS and HALT index were the highest in the group of patients with combined angiodysplasias, amounting to 9.02±0.09:20.9±0.2 and 21.1±0.2 points, the lowest with isolated hypo/aplasias and pathological PA deformations 6.5±0.04:15.5±0.1: 16.5±0.1 and 6.6±0.04:15.5±0.1:16.5±0.1, respectively. Conclusions: Congenital precerebral angiodysplasia can lead to the development of migraine, most often migraine with aura, while they have a high intensity headache, with a decrease in the daily activity of patients and the need for medical care.